On ways to reduce the energy supply costs in Russia - S. A. Nekrasov; V. V. Klimenko (Модернизация, инновация, развитие, 2024)
Purpose: is to research of ways to reduce the energy supply costs for Russian consumers.Methods: the analysis of the transformation of the electric power industry was carried out using the tools of tectology and system economic theory.Results: the key reason for the constant increase in the cost of energy supply has been identified, which is the transition from a systematic approach to energy development aimed at increasing general economic efficiency to maximizing the economic performance of independent energy companies. The need to adjust the basic principles laid down in the concept of electric power industry development is substantiated.Conclusions and Relevance: the result of the successful completion of the reform of the Russian electric power industry is a steady influx of significant investments into the industry over the course of decades. But despite the increase in power system capacity, which is outstripping the dynamics of electricity demand, the need for the most expensive peak power sources and energy storage systems is growing, which leads to an increase in electricity prices in addition to the investment component. A positive feedback has been identified that reduces the structural stability of the energy sector, namely: between rising electricity prices; reduction of electricity consumption from the network as a result of the installation of their own generation by some consumers; increasing costs of generating and network companies; more intensive growth in electricity prices and increased motivation to install their own generation for that part of consumers who continue to use grid electricity. The ways are proposed and the solutions are considered aimed at forming new connections between participants in the single technological process of production, transmission and consumption of energy resources, with the aim of reducing the energy supply costs and improving the specific performance indicators of the energy system, and in the future reducing the costs of integrating renewable energy sources into it.